You're invited - Jayatissa, Amanda (Berkley, 2022)
"From the author of My Sweet Girl comes a dangerously addictive new thriller about a lavish Sri Lankan wedding celebration that no one will ever forget. When Amaya is invited to Kaavi's over-the-top wedding in Sri Lanka, Amaya is surprised and a little hurt to hear from her former best friend after so many years of radio silence. But when Amaya learns that the groom is her very own ex-boyfriend, she is consumed by a single thought: She must stop the wedding from happening, no matter the cost. But Amaya might not be the only one with a plan to keep the bride from getting her happily ever after. When Kaavi goes missing and is presumed dead, the evidence points towards Amaya. Caught between excessive Sri Lankan wedding celebrations, old wounds, and dark secrets, will Amaya be able to prove she's being framed for a murder she's almost positive she didn't commit?"--